Behind the pathology of macrophage-associated demyelination in inflammatory neuropathies: demyelinating Schwann cells - Park, Hwan Tae; Kim, Young Hee; Lee, Kyung Eun; Kim, Jong Kuk (SPRINGER BASEL AG, 2020)
In inflammatory peripheral demyelinating disorders, demyelination represents segmental demyelination in which the myelin sheath of a myelinating Schwann cell (SC) is completely removed by macrophages or a partial myelin degeneration in the paranode occurring due to autoantibodies attacking the node/paranode. For the segmental demyelination from living myelin-forming SCs, macrophages infiltrate within the endoneurium and insinuate between myelin lamellae and the cytoplasm of SCs, and the myelin is then removed via phagocytosis. During the macrophage invasion into the SC cytoplasm from the node of Ranvier and internodal areas, the attacked SCs do not remain quiescent but transdifferentiate into inflammatory demyelinating SCs (iDSCs), which exhibit unique demyelination pathologies, such as myelin uncompaction from Schmidt-Lanterman incisures with myelin lamellae degeneration. The longitudinal extension of this self-myelin clearance process of iDSCs into the nodal region is associated with the degeneration of nodal microvilli and paranodal loops, which provides a potential locus for macrophage infiltration. In addition to the nodal intrusion, macrophages appear to be able to invade fenestrated internodal plasma membrane or the degenerated outer mesaxon of iDSC. These SC demyelination morphologies indicate that the SC reprogramming to iDSCs may be a prerequisite for macrophage-mediated inflammatory demyelination. In contrast, paranodal demyelination caused by autoantibodies to nodal/paranodal antigens does not result in iDSC-dependent macrophage infiltration and subsequent segmental demyelination. In the context of inflammatory demyelination, the novel perspective of iDSCs provides an important viewpoint to understand the pathophysiology of demyelinating peripheral neuropathies and establish diagnostic and therapeutic strategies.
Keywords: EXPERIMENTAL ALLERGIC NEURITIS; EXPERIMENTAL AUTOIMMUNE NEURITIS; UNCOMPACTED MYELIN LAMELLAE; PERIPHERAL-NERVE; WALLERIAN DEGENERATION; LANTERMAN INCISURES; CAJAL BANDS; IN-VIVO; EXPRESSION; AUTOANTIBODIES